Aggregation‐induced demulsification triggered by the hydrophilic fabric for the separation of highly emulsified oil droplets from water. Issue 1 (14th October 2021) - Zhang, Yu‐Rong; Meng, Bi‐Wei; Hao, Bin; Ma, Peng‐Cheng
Abstract: A functional fabric with hierarchical structure consisting of basalt fibre fabric as a substrate and polyvinyl alcohol as a coating was developed, aiming at providing a low cost and high‐performance way to separate highly emulsified oil in water. The coating functioned as a hydrophilic gate for the penetration of water in the emulsion, whereas the micro‐channels formed in the fabric offered capillary force for the continuous flow of water. The synergy of these two materials led to the increase on the oil concentration in the liquid, which in turn enhanced the collision of emulsified oil droplets to aggregate into large ones in the emulsion and resulted separation from the water. Based on these findings, an aggregation‐induced demulsification process was proposed to explain the above phenomenon, and the mechanism was confirmed by studying the distribution of oil droplets in emulsion with a controlled separation degree. Abstract : A functional fabric showed excellent performance to separate highly emulsified oil in water, aggregation‐induced demulsification process was proposed to explain the above phenomenon, and this was confirmed by studying the distribution of oil droplets in emulsion with a controlled separation degree.